(untitled) (Research, Society and Development, 2021)
The present study aims to understand in what personal conditions the managers who work with adolescent offenders performed their remote work in the Coronavirus pandemic. For that, qualitative research is used (Flick, 2013), through online questionnaires, submitting the results to a content analysis (Gil, 2002). The data indicate that managers are very interested in seeking help to be able to help both teachers and the community. In addition, it was noticed that they are experiencing an emotional impact because they are working remotely, but even so, they are seeking to improve and adapt the forms of dialogue in the face of reality. The managers are very interested in seeking assistance from the Department of Education, following all the decrees issued. In addition, it has been talking with health care and other actions that include everything from food donation to clothes. Therefore, it is possible to consider that the education of adolescent offenders took place within the available possibilities, in view of the investigation with the managers.